Strategi dan Tantangan Berbisnis dalam Lingkup Umum di Era Globaliasi 4.0 - Wulandari; Retno Indriyani; Dwi Astuti (CV. ITTC INDONESIA, 2025)
In the era of globalization 4.0, business strategies and challenges have undergone significant transformation, impacting how companies operate. This article analyzes various strategies that can be implemented by business actors to remain competitive in an ever-changing environment. Approaches such as digitalization, technological innovation, and human resource development are key components of modern business strategies. Additionally, challenges such as market uncertainty, changes in consumer behavior, and the rapid impact of regulations are identified as obstacles that must be confronted. This research employs case studies to illustrate how some companies have successfully navigated these challenges through the adoption of various adaptive strategies. The findings indicate that collaboration between the public and private sectors, as well as investment in information technology, is crucial for driving sustainable economic growth in this era. In conclusion, while there are many challenges, the opportunities presented by globalization 4.0 can be leveraged through the right strategies, which in turn will provide significant competitive advantages for companies